Kajian Literatur tentang Faktor-Faktor Determinan Turnover Karyawan Kurir pada Industri Ekspedisi dan Logistik - Priest Winka Sajida; Jacobus Rico Kuntag (Commodities, Journal of Economic and Business, 2026)
Courier employee turnover in the freight forwarding and logistics industry affects service continuity, operational stability, delivery quality, and the cost of recruiting and training new workers. This study aims to identify and map the factors that affect courier turnover through a descriptive literature review. Data were obtained through searching, selection, mapping, and narrative synthesis of various literature relevant to turnover, courier work, logistics industry, as well as platform-based work dynamics and algorithmic management. The results of the study show that courier turnover is influenced by work, organizational, economic, technological, and psychological factors. The main factors include high workload, delivery target pressure, uncertainty of income and incentives, occupational safety risks, low organizational support, low work attachment, and dissatisfaction with the workforce management system. In addition, the use of applications and algorithms in work management increases the pressure through digital surveillance and automated performance assessments that are often not balanced by adequate work protections. This study confirms that courier turnover is the result of a complex interaction between working conditions, organizational systems, and workers' perceptions of justice and sustainability of work. Therefore, retention efforts need to be focused on improving work design, compensation, organizational support, work safety, and more humane technology management.